O efeito do narcisismo dos gestores na agressividade de decisões estratégicas e no desempenho empresarial - Cardoso, Vanessa Ingrid da Costa (2022)
In addition to the company's attitude in the market, strategic decisions portray the characteristics of the company's decision-maker and culminate in corporate performance. In this context, it is also understood that the professionals' performance in determining corporate decisions is directly affected by their lived experiences, values, and, mainly, their personality. Narcissism is seen as a personality trait that significantly affects the choices made by executives in organizations, as research supports that narcissists typically draw strategies prone to aggressive decision-making. Considering that the Chief Executive Officer (CEO) and the Chief Financial Officer (CFO), identified as members of the top management team, make decisions in companies associated, among other aspects, with their personality, it can be assumed that the aggressiveness of decisions strategies is higher when it comes to managers with higher levels of narcissism. Thus, under the view that companies are reflections of their main managers, this study is based on the Upper Echelons Theory, in which the characteristics of individuals occupying positions at high corporate levels, measured through analysis of speech and relative remuneration, affect their decisions and, consequently, organizational performance. This research advocates that the narcissistic personality characteristics of top executives affect decisions regarding fiscal aggressiveness, earnings management, company merging, and acquisition processes, which can be influenced by both the CEO and the CFO. Thus, the present research aims to analyze the effect of high-level managers' narcissism on the aggressiveness of strategic decisions and business performance. The study sample brings together 762 companies listed on the American stock exchange, arranged in an unbalanced panel from 2002 to 2020. Given the results, it was found that the hypotheses were not rejected for the set of companies in which narcissism was measured through relative remuneration, in the CFO models, especially in the models in which the CFO's narcissism was an explanatory variable of aggressiveness in earnings management and in the model in which the CFO's narcissism was an explanatory variable of performance; in general, in these models, the Upper Echelons Theory (UET) was confirmed.